Eksistensi Permainan Tradisional sebagai Warisan Budaya Bangsa - Gustiana Mega Anggita (Journal of Sport Science and Education, 2019)
Objective: to determine the existence, amount and types of traditional games which are in the district of Semarang. Methods: This study was descriptive qualitative research with survey method. Samples from this study is the physical education teacher and elementary school students who are in the district of Semarang. Data collection techniques in this study using questionnaires, interviews and documentation. Results: The results of the study show the following: (1) There are various traditional games in Semarang District; (2) the number of traditional games contained in Semarang District of ten traditional game consists of: Bentengan, Gobak Sodor, Sunda Manda, Bakiak, Bintang Bergilir, Bola Bakar, Egrang, Rok Dodok, Kucing Tikus dan Ular Naga; (3) traditional games which are in the district of Semarang who often played the children of eight games consist of: Bentengan, Gobak Sodor, Sunda Manda,Kucing Tikus, Bintang Bergilir dan Bola Bakar. Conclusion: The traditional game contained in Semarang district as many as ten games and traditional games are often played in Semarang district as many as six games.